Short Communication: The genetic diversity and agronomical characters of local cultivars of tidal rice in East Kalimantan, Indonesia - RUSDIANSYAH RUSDIANSYAH; TJATJUK SUBIONO; WIDI SUNARYO; ANDI SURYADI; SULASTRI SULASTRI; SAMID ANJASMARA (Society for Indonesian Biodiversity, 2017)
Rusdiansyah, Subiono T, Sunaryo W, Suryadi A, Sulastri, Anjasmara S. 2017. Short Communication: The genetic diversity and agronomical characters of local cultivars of tidal rice in East Kalimantan, Indonesia. Biodiversitas 18: 1289-1293. Availability of local rice germplasm is very important for plant breeding, especially in the improvement of the genetic diversity. The objectives of the research were to study the genetic diversity and agronomical characters of local characters of tidal rice in East Kalimantan. The research was conducted from May to October 2014 in the Village of Sidomulyo, Anggana Sub-District, Kutai Kertanegara District, East Kalimantan. The experiment was arranged in a randomized complete block design (RCBD) with five replications. Eight selected local tidal rice cultivars from East Kalimantan (Pandan Ungu, Kambang, Amas, Roti, Pudak, Sikin Merah, Sikin Putih and Popot) were used in this experiment as plant materials. The results showed that there was wide genetic diversity among local tidal-rice cultivars selected from East Kalimantan. Number of productive tillers, the percentage of empty grain per panicle, 1000 grain weight and yield per hectare can be used as selection criteria for local lowland rice cultivars from East Kalimantan because they have a high value of heritability (h2 bs), phenotype and genotype and coefficient of variation (PCV and GCV). Pandan Ungu, Kambang, Amas, Roti and Sikin Merah cultivars potential to be used as parents in the breeding program.